1997
DOI: 10.1159/000246043
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Effects of Povidone-Iodine on Relevant Microorganisms: An Electron-Microscopic and Biochemical Study

Abstract: The aim of this study was to elucidate the effects of povidone-iodine (PVP-I) on cell ultrastructure by electron microscopy and to monitor changes in enzyme activity and nucleotide efflux. Staphylococcus aureus, Escherichia coli and Candida albicans, medically relevant gram-positive, gram-negative and yeast microorganisms, served as models. In the presence of PVP-I, rapid partitioning of the cytoplasm and pronounced coagulation of nuclear material was noted. E. coli and S. aureus showed no major structural wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 0 publications
0
79
0
7
Order By: Relevance
“…Senyawa iodine memiliki sifat yang sitotoksik sehingga mampu membunuh sel bakteri. 7 Povidone iodine dapat merubah struktur dan fungsi dari protein dan enzim sel dan merusak fungsi sel bakteri dengan jalan menghambat perlekatan hidrogen dan merubah struktur membran sel, 8 selain itu juga menghambat terjadinya sintesis protein oleh bakteri melalui proses oksidasi thiol di dalam asam amino sistein. 9 Salah satu keuntungan povidone iodine adalah mampu menghambat sintesis glucosyltransferase (GTF) dan fructosyltransferase (FTF) oleh S.mutans.…”
Section: Pembahasanunclassified
“…Senyawa iodine memiliki sifat yang sitotoksik sehingga mampu membunuh sel bakteri. 7 Povidone iodine dapat merubah struktur dan fungsi dari protein dan enzim sel dan merusak fungsi sel bakteri dengan jalan menghambat perlekatan hidrogen dan merubah struktur membran sel, 8 selain itu juga menghambat terjadinya sintesis protein oleh bakteri melalui proses oksidasi thiol di dalam asam amino sistein. 9 Salah satu keuntungan povidone iodine adalah mampu menghambat sintesis glucosyltransferase (GTF) dan fructosyltransferase (FTF) oleh S.mutans.…”
Section: Pembahasanunclassified
“…Those studies, however, used a planktonic antibacterial assay in vitro. Schreier and co-workers found that even lower PVPiodine concentrations resulted in an efficacy maximum against Staphylococcus aureus, Candida albicans and Escherichia coli under laboratory conditions [14]. Yet, bacteria imbedded in the biofilm with its protective and adhesive extracellular matrix are much less susceptible to antiseptics [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…As an antibacterial agent, chlorhexidine has been widely used, but the clinical efficiency is questionable as an adjunct to scaling and root planning in the available formulations [13]. PVP-iodine could be a candidate as it represents an antiseptic with a broad antibacterial spectrum covering Grampositive and -negative bacteria and mycobacteria, [14] Staphylococcus spp., Candida albicans [15] and periopathogenic germs. [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, solution with 1:10,000 dilution still presents bactericidal activity. 64,65 Potential disadvantages of povidone-iodine solution are tendency for an irritation to the applied site, cytotoxicity and staining of the tissues. Although in some in-vivo and animal studies the cytotoxicity was observed, these results were not confirmed in humans.…”
Section: E Povidone-iodine Solutionmentioning
confidence: 99%